Iqbal Poetry & Modernization of Islamic Thought: کلام اقبال اور اسلامی فکر کی تشکیل جدید - Taj, Shazia; Naqvi, Dr. Sadaf (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Freedom of thought is an essence. The people of nation who have freedom of thought play an active role in the development of their society. Iqbal's poetry & political thought are intertwined. According to Iqbal , the principle of Islam is "Ijtehad ". It gives the thinkers the opportunity to solve new problems & interpret the principles of " Sharia" in different ways. Iqbal is against the politics devoid of religion. According to Iqbal, the state is the name of development of structure & organisation of collective life. The West is devoid of the insight of scientific observations. Iqbal emphasises the importance of juxtaposing insight with knowledge. Iqbal emphasises the construction of new science of knowledge, new interpretation of Islamic jurisprudence & reconstruction of Islamic life. According to Iqbal , education is the only means to achieve these goals.